Communicative Tasks And Speaking Proficiency Level On The Choice Of Communication Strategies Use By Yemeni Efl Students - Hasan Abdullah, Lamis Abdulrahman (2015)
The purpose of this study is to investigate the relationship between the communicative tasks and speaking proficiency level on the choice of communication strategies used by the first year students at Aden University- Yemen. The study focuses on the two main variables the communicative tasks and the speaking proficiency level and how they affect the students' choice of communication strategies. The study used two main theories of communication strategies (CSs) the interactional perspectives and the psycho linguistic perspective of communication strategies. The 82 participants of the study were the first year students of English department at University of Aden-Yemen in the academic year 2013-2014.